Discovery of Imidazopyridines as Potent Inhibitors of Indoleamine 2,3-Dioxygenase 1 for Cancer Immunotherapy - Zhang, Liping (ACS Med Chem Lett, 2021)
[Image: see text] Indoleamine 2,3-dioxygenase 1 (IDO1) has been identified as a target for small-molecule immunotherapy for the treatment of a variety of cancers including renal cell carcinoma and metastatic melanoma. This work focuses on the identification of IDO1 inhibitors containing replacements or isosteres for the amide found in BMS-986205, an amide-containing, IDO1-selective inhibitor currently in phase III clinical trials. Detailed subsequently are efforts to identify a structurally differentiated IDO1 inhibitor via the pursuit of a variety of heterocyclic isosteres, leading to the discovery of highly potent, imidazopyridine-containing IDO1 inhibitors.